Organizing reflection to address collective dilemmas: Engaging students and professors with sustainable development in higher education. (1st December 2018) - Brunstein, Janette; King, Jeff
Abstract: Critical reflection and transformative learning theories generally place emphasis on individual change, giving little consideration to the organizational and societal aspects. Consequently, it is individual and not collective dilemmas that are reinforced in higher education. However, a call for an education initiative for sustainable development requires a shift in focus. This article considers transformative learning for sustainability within the context of an American university whose mission encompasses being a center for excellence in transformative teaching and learning. The analysis is divided into three parts as follows: The organizing reflection process of the university; b) how professors concretize collective dilemma in their teaching; and c) student engagement levels in collective dilemmas with regard to the tenets of service learning and civic engagement. Despite its unique trajectory, this qualitative case study presents an argument – in order to achieve a paradigmatic shift toward sustainability, we need to create an organizing process of reflection to address collective dilemmas and engage faculty and students in a continuous and institutionalized transformative learning process. The results show the potential and limitations of the analyzed experience; further, it addresses the theoretical implications and practical insights for fostering critical reflection and transformative learning toward sustainability.